The phenomenon of translatability in the Europeanization of the Law. - Olldashi, Enkeleda (Academicus, 2013)
The integration of legal systems in European is one of the most important issues. This process has started by the fact that there are significant differences between the civil law and common law system and between the legal families in it. A law (at domestic or international level) should not be viewed against the backdrop of the historical, political, cultural, social and economic context in which they function. In order to shed further light for our readers, we analyze by emphasizing the significant differences between the civil law and common law system on one side and the legal families that are part of the same legal system, either "Civil" or "Common," on the other side. The Europeanization of law refers to the communization of the law by EU institutions and to a process that aims at creating a common Europe legal system. In the end, either in medium or long term, the Europeanization is contributing to the so-called non-mandatory or soft harmonization of private law. It is in the best interest of the EU to seek adequate judicial instruments to accommodate the massive numbers of laws deriving from different Civil Law and the Common law systems.